1988
DOI: 10.2307/1130396
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Patterns of Attachment: A Meta-Analysis of the Strange Situation

Abstract: VAN IJZENDOORN, MARINUS H , and KROONENBERG, PIETER M Cross-cultural Patterns of Attachment A Meta-Analysts of the Strange Situation CHILD DEVELOPMENT, 1988, 59, 147-156 Crosscultural research usmg Amsworth's Strange Situation tends to rely on incomplete Information and to concentrate on individual rather than aggregated samples In this study, a widei perspective is taken by exammmg almost 2,000 Strange Situation classifications obtamed m 8 different countries Differences and similanties between distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
132
4
10

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(160 citation statements)
references
References 37 publications
14
132
4
10
Order By: Relevance
“…Singer et al (1985) found that 11 of 19 (58%) inter-racial adoptees were insecurely attached, as compared to 7 of 27 (26%) nonadoptees. Compared to other studies (Van IJzendoorn, Goldberg, Kroonenberg, & Frenkel, 1992;Van IJzendoorn & Kroonenberg, 1988) the inter-racially adopted group shows an overrepresentation of insecure attachment relationships.…”
Section: Attachment In Adoptive Familiescontrasting
confidence: 75%
See 1 more Smart Citation
“…Singer et al (1985) found that 11 of 19 (58%) inter-racial adoptees were insecurely attached, as compared to 7 of 27 (26%) nonadoptees. Compared to other studies (Van IJzendoorn, Goldberg, Kroonenberg, & Frenkel, 1992;Van IJzendoorn & Kroonenberg, 1988) the inter-racially adopted group shows an overrepresentation of insecure attachment relationships.…”
Section: Attachment In Adoptive Familiescontrasting
confidence: 75%
“…The percentage of secure attachment in our sample (74% at 12 months and 75% at 18 months) is not lower than the percentage found in normative studies (e.g. 68% secure attachment in pooled Dutch samples; Van IJzendoorn & Kroonenberg, 1988). A stability of 68% (Cohen's kappa .36) was observed in our group: 46 of 58 infants were secure at both 12 and 18 months, 8 of 21 infants remained insecure.…”
Section: Infant-mother Attachmentcontrasting
confidence: 66%
“…First, such a comparison seems justified by the fact that libidinal development is universal, the same for Belarusian and French children, although we were unable to find any empirical study assessing especially this Freudian conjecture. Second, some readers might argue that there are limitations or biases related to cross-cultural comparisons of sociocultural norms and values (Van IJzendoorn & Kroonenberg, 1988), underlining, for example, that different attachment styles and norms have been established for German children as compared to American ones, based on different child-rearing practices in these two cultures. But the available literature (Speckhard & Mufel, 2003), although scarce, did not indicate any major differences between the educational styles of Western parents and Belarusian ones, as suggested by the authors in the conclusion of their study: "Belarus women who have adverse responses are very similar across these two divergent cultures" (p. 3).…”
Section: Study Of a Single Case Of Mother-child Interactionsmentioning
confidence: 99%
“…Skewed distributions of attachment relationships, including that found by Sagi and his colleagues, have raised concern that the stränge Situation may not be cross-culturally valid (Grossmann, Grossmann, Spangler, Suess, & Unzner, 1985;. However, recent secondary analyses and meta-analyses (Sagi, Van IJzendoorn, & Koren-Karie, 1991;Van Uzendoorn & Kroonenberg, 1988), äs well äs analyses of cross-national data (Lamb, Thompson, & Gardner, 1985;Sagi, 1990;Van Uzendoorn, 1990), have indicated that this procedure is valid for assessing universal communicative patterns between adults and infants that may be aifected by stress (Van IJzendoorn & Kroonenberg, 1988) or by cultural preferences (Sagi, 1990). Clearly, more research was needed to find precursors of attachment relationships in kibbutz children so äs to understand the unusual rates of insecure relationships.…”
Section: Infants'relations With Parentsmentioning
confidence: 99%